STRUCTURE OF AQUEOUS DECYLTRIMETHYLAMMONIUM BROMIDE SOLUTIONS AT THE AIR WATER INTERFACE STUDIED BY THE SPECULAR REFLECTION OF NEUTRONS - Lee, E; Thomas, R; Penfold, J; Ward, R (1989)
The technique of specular reflection of neutrons has been used to investigate the adsorption of decyltrimethylammonium bromide (DTAB) at the aqueous solution/air interface over the concentration range 0.002-0.1 M. Hydrogen-deuterium substitution in both surfactant and solvent has been used to highlight different features of the adsorbed layer and to distinguish between solvent and solute in this layer. At the lowest concentration the thickness of the adsorbed layer is 16 ± 3 Å, indicating that the molecules are aligned with the long axis perpendicular to the interface. At a concentration of 0.05 M, where the monolayer is essentially complete, the thickness is found to be 21 ± 1 Å. This suggests that in the more closely packed monolayer the head groups, which carry a positive charge, may be "staggered" in order to minimize their mutual repulsion. A detailed analysis of the structure at 0.05 M indicates that the layer may be divided into two regions: a head group region, 6 Å thick, containing the trimethylammonium head group, counterion, water, and about 10% of the alkyl chain tails; and a tail group region, 15 Å thick, containing only tail groups. The area per molecule of surfactant at the saturated monolayer is found to be 58 ± 5 Å2. Above the critical micelle concentration (0.065 M) the structure of the interface is more complex. The monolayer itself is some 15% more dense than the saturated monolayer formed below the cmc. The shape of the reflectivity profile is shown to be consistent with some ordering of the micelles beneath the surface, separated from the monolayer by a thin layer of water, which contains no surfactant and which has a density more akin to that of water in hydrates. Mixtures of DTAB and sodium decanoate have also been investigated. Equimixtures of the two oppositely charged surfactants are much more strongly adsorbed than either of the two individual components. Even at the low total concentration of 0.01 M the area per surfactant molecule of the mixed monolayer is 36 Å2 compared with 73 Å2 for 0.01 M DTAB alone. © 1989 American Chemical Society.